Person-environment resources for aging well: environmental docility and life space as conceptual pillars for future contextual gerontology - Wahl, Hans-Werner; Gerstorf, Denis (The gerontologist, 2020)
A variety of different disciplines in the study of aging have long acknowledged that individual functioning and development are profoundly shaped by the contexts people live in. The Gerontologist has played a central role in publishing and fostering theoretical and empirical work geared toward better understanding many of the questions that revolve around the how and the why. To illustrate, we consider in a first step the environmental docility hypothesis and the life space construct as two landmark concepts published in The Gerontologist and review how these—in conjunction with the later introduced proactivity perspective—have shaped for decades and continue to shape the larger field of (contextual) gerontology. In a second step, we discuss how these two entirely separate conceptualizations could be integrated in a late pas-de-deux. In doing so, we also make use of Wahl & Gerstorf's conceptual framework for studying COntext Dynamics in Aging (CODA) to discuss how these classic concepts can promote future gerontological research.
GSA’s 75th Anniversary: Forum
Gesehen am 24.03.2021